Hydraulics Performance of Coastal Flood Control in Madukoro Area, Semarang City, Indonesia - Dian Wahyu Jatmiko (Journal of the Civil Engineering Forum, 2018)
Madukoro area located on the northern coast of Semarang City has been prone to flooding caused by rainfall and seawater high-tide. Ineffective flood control management and land subsidence are considered as the cause of this problem. In order to understand land subsidence effect and flood control performance, location, water surface height of the inundation in West Flood Canal, western part of Madukoro area need to analyze. Flood analysis was conducted using HEC-HMS software and rational method. Flow hydraulics on five channels, i.e. the West Flood Canal, Ronggolawe River, Karangayu River, Arterial Channel and Madukoro were analyzed using HEC-RAS software. Increasing levee level and additional water pumps in Madukoro and Ronggolawe were chosen as flood control alternatives. Its performance was investigated through software simulation. The results showed total runoff volume in all drainage channels for 2-years return period discharge was about 80% of capacity with 0.7 m water depth. Runoff volume in West Flood Canal with 50-years return period discharge was about 40%. Land subsidence 4 cm/year affected the water level increase on West Flood Canal. Operation of 2 - 4 pump units could not significantly decrease water level at flood peak, yet increase flood recession time 6 - 8 hours.